Cognitive Behavioral Therapy in Endometriosis, Psychological Based Intervention: A Systematic Review - Donatti, Lilian; Malvezzi, Helena; Azevedo, Bruna Cestari de; Baracat, Edmund Chada; Podgaec, Sergio (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Introduction Endometriosis is an inflammatory disease that affects women of reproductive age, causing pain and the possibility of infertility. Endometriosis was associated to low life quality and research shows the impact of endometriosis in several areas of life, justifying how these patients are more likely to develop depression, anxiety, and stress.Objective The aim of the present systematic review was to explore the field of psychology in endometriosis, identifying studies that used the cognitive behavioral therapy technique as a treatment for endometriosis and chronic pelvic pain.Methods The keywords used were Endometriosis and Behavioral Therapy; Behavioral Disciplines and Activities; Cognitive Behavioral Therapy; Mental Health; Psychological Techniques; Psychology; Psychotherapy; Mental Health Services; and the search was performed in the following databases: PubMed/Medline, Scielo, Lilacs, and Capes. The study followed the PRISMA guidelines and all studies whose intervention strategy used was related to cognitive-behavioral therapy were considered.Results Of the 129 articles found, only 5 were selected, and it was possible to identify that the psychological intervention whose approach brought cognitive-behavioral therapy techniques promoted a decrease in the sensation of pain, improvements in the scores of depression and stress, and significant changes in aspects of quality of life such as vitality, physical and social functioning, emotional well-being, control, and autonomy.Conclusion Cognitive-behavioral therapy can be very promising to take care of the emotional side of those who have endometriosis However, the present systematic review highlights the need to develop more structured studies with consistent, clear and replicable methods to reach a psychological intervention protocol for patients who live with this gynecological-physical-emotional condition.
Keywords: endometriosis; cognitive behavioral therapy; psychological intervention; chronic pelvic pain; quality of life; systematic reviews